Cross‐Electrophile C(sp2)−Si Coupling of Vinyl Chlorosilanes. (7th December 2020) - Duan, Jicheng; Wang, Ke; Xu, Guang‐Li; Kang, Shaolin; Qi, Liangliang; Liu, Xue‐Yuan; Shu, Xing‐Zhong
Abstract: The cross‐electrophile coupling has become a powerful tool for C−C bond formation, but its potential for forging the C−Si bond remains unexplored. Here we report a cross‐electrophile Csp 2 ‐Si coupling reaction of vinyl/aryl electrophiles with vinyl chlorosilanes. This new protocol offers an approach for facile and precise synthesis of organosilanes with high molecular diversity and complexity from readily available materials. The reaction proceeds under mild and non‐basic conditions, demonstrating a high step economy, broad substrate scope, wide functionality tolerance, and easy scalability. The synthetic utility of the method is shown by its efficient accessing of silicon bioisosteres, the design of new BCB‐monomers, and studies on the Hiyama cross‐coupling of vinylsilane products. Abstract : Organosilanes: A new C−Si bond‐forming reaction via C−X and Si−Cl cleavage was achieved by reductive nickel catalysis. This method bridges the gap between the cross‐electrophile coupling and organosilicon chemistry. It offers very mild reaction conditions for facile and precise synthesis of structurally versatile vinylsilanes that have found applications in many fields.